NANOCON 2019 Conference Proeedings 2020
DOI: 10.37904/nanocon.2019.8769
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Plasma Cleaning and Activation of Float Soda-Lime Glass Prior to Lamination Processing

Abstract: Precleaning of float glass is an important step in manufacturing processes based on combining its surface with other materials. Cleanness, together with surface roughness and chemical activity affect adhesion properties of the substrate that are crucial for the quality of the final product. Atmospheric pressure plasma pretreatment was studied as a dry alternative to conventional wet cleaning methods of glass, with the aim at industrial requirements. Diffuse coplanar surface barrier discharge (DCSBD) and multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The measured values and ageing trend are in a quite good accordance with the study on SLG of Homola et al [7]; however, the results presented here vary in uncertainties that are significantly lower, particularly with the use of longer exposure times 5, 7 and 10 s. Besides better stability, DCSBD "Air-pillow" plasma treatment also showed better reproducibility, which is evident from the similarity of WCAs after longer exposures. Non-uniformity and non-reproducibility of treatment effects could be caused by insufficient removal of organic contamination with very short exposure time to DCSBD plasma [5]. Another possible source of uncertainty is unprecise guidance of treated surface, where 0.3 mm is the advisable distance of the surface from the ceramic of discharge system that is commonly used for DCSBD [2] in order to fully benefit from the diffuse component of its plasma generated in air at atmospheric pressure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The measured values and ageing trend are in a quite good accordance with the study on SLG of Homola et al [7]; however, the results presented here vary in uncertainties that are significantly lower, particularly with the use of longer exposure times 5, 7 and 10 s. Besides better stability, DCSBD "Air-pillow" plasma treatment also showed better reproducibility, which is evident from the similarity of WCAs after longer exposures. Non-uniformity and non-reproducibility of treatment effects could be caused by insufficient removal of organic contamination with very short exposure time to DCSBD plasma [5]. Another possible source of uncertainty is unprecise guidance of treated surface, where 0.3 mm is the advisable distance of the surface from the ceramic of discharge system that is commonly used for DCSBD [2] in order to fully benefit from the diffuse component of its plasma generated in air at atmospheric pressure.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments on standard DCSBD are being realized with samples placed in holders that are guided in contact with the ceramic. DCSBD "Air-pillow" was designed for treatment of flat smooth large-area surfaces applying pneumatic levitation to perform contactless guidance [5] . "Roll" DCSBD reactor works with a concavely curved discharge unit and is intended for treatment of flexible materials that can be bent to the radius of 15 cm of the reactor roll [6].…”
Section: Methodsmentioning
confidence: 99%
“…Especially for large-area flat materials, e.g. plates of soda-lime glass to be plasma-treated before application of a coating, it is technically challenging to maintain a precise distance over the entire area, and such an issue can significantly increase the cost of the line [14]. For an R2R line, which usually employs lightweight, flexible materials such as plastic foils, the plasma-treated surfaces of non-conductive materials result in a fast accumulation of charges on its surface, leading to the attraction of the plasma-treated material towards the plasma.…”
Section: Advantages and Peculiarities Of Coplanar Dbdmentioning
confidence: 99%
“…They observed that there was a significant improvement in toner fixing after plasma treatments [15]. Plasma treatments of soda‐lime glass and ultra‐thin flexible glass with diffuse coplanar surface barrier discharge plasma showed a rapid significant hydrophilicity improvement due to two mechanisms: purification from air pollutants and simultaneous chemical activation by oxygen‐based functional groups [16]. In another study performed diffuse coplanar surface barrier discharge plasma surface treatment of soda‐lime glass.…”
Section: Introductionmentioning
confidence: 99%
“…In another study performed diffuse coplanar surface barrier discharge plasma surface treatment of soda‐lime glass. According to their results, diffuse coplanar surface barrier discharge plasma treatment proved significant improvement of safety glass strength and suitability of the diffuse coplanar surface barrier discharge plasma system for fast large‐area in‐line production in factory conditions [17]. Studies point to subtle differences in the effect of the applied plasma processing atmosphere on the resulting ceramic nanocomposites, particularly the use of a combination of needleless electrospinning technology and low‐temperature diffuse coplanar surface barrier discharge plasma processing in three different atmospheres: oxidizing ‐ air, reducing ‐ dioxygen and inert ‐ dinitrogen atmospheres, to prepare and modify composites Titanium dioxide/polyvinylpyrrolidone microfibers with gradient composition [18].…”
Section: Introductionmentioning
confidence: 99%